A Retentive Consumer-Buying Behavior towards Online Purchase Decision-Making Process in Kathmandu Valley - Adhikari, Nikesh; Pradhan, Radhe Shyam (Nepalese Journal of Economics, 2025)
This study examines the effect of a retentive consumer-buying behavior towards online purchase decision making process in Kathmandu valley. Consumer buying behavior is the dependent variable. The selected independent variables are trust, quality, post purchase experience, consumer satisfaction, and lower price. The primary sources of data is used to assess the opinions of respondents regarding trust, quality, post purchase experience, consumer satisfaction, and lower price. The study is based on the primary data of 100 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of a retentive consumer-buying behavior towards online purchase decision-making process in Kathmandu valley. The study showed a positive impact of trust on consumer buying behavior. It indicates that trust leads to increase in consumer buying behavior. Similarly, the study showed a positive impact of quality on consumer buying behavior. It indicates that quality leads to increase in consumer buying behavior. Likewise, the study showed a positive impact of post purchase experience on consumer buying behavior. It indicates that post purchase experience leads to increase in consumer buying behavior. Further, the study also showed a positive impact of consumer satisfaction on consumer buying behavior. It indicates that post purchase experience leads to increase in consumer buying behavior. In addition, the study showed a positive impact of consumer satisfaction on consumer buying behavior. It indicates that consumer satisfaction leads to increase in consumer buying behavior. Moreover, the study showed a positive impact of lower price on consumer buying behavior. It indicates that lower price leads to increase in consumer buying behavior.